Pemanfaatan Media Interaktif Baamboozle pada Pembelajaran Bahasa Indonesia - Tsurayya, Nabhana Aida (Universitas Suryakancana, 2023)
This article describes the use of Bamboozle in learning Indonesian. The research approach uses a qualitative approach with data in the form of words. Library research is carried out by collecting data and information from library sources, such as articles, books, journals, documents, and other library sources. The results of the study show that web-based media on Bamboozle include providing independent learning opportunities, making questions by creating an account on Bamboozle for free, and how to play Bamboozle on Indonesian language material. The disadvantages of Bamboozle include very limited features, the creation of a question maker account and answering questions are not distinguished, there is no access permission to start the game, the game can only be played per team, there are no instruments on Bamboozle, only the back sound when selecting the answer, at the time using media makes it possible for passive students While the advantage of Bamboozle is to access Bamboozle without having to create an account, there are various questions, and it can be used for each level of education. Bamboozle can be accessed via a laptop or cellphone.Keywords: Baamboozle, Indonesian; instructional Â mediaABSTRAKArtikel ini mendeskripsikan penggunaan Bamboozle dalam pembelajaran Bahasa Indonesia. Pendekatan penelitian menggunakan pendekatan kualitatif dengan data berupa kata-kata. Penelitian kepustakaan dilakukan dengan mengumpulkan data dan informasi dari sumber pustaka, seperti artikel, buku, jurnal, dokumen dan sumber pustaka lainnya. Hasil penelitian menunjukkan bahwa media berbasis web pada BamboozleÂ di antaranya menyediakan kesempatan belajar mandiri, membuat soal dengan membuat akun di Bamboozle secara gratis.dan cara bermain Bamboozle pada materi Bahasa Indonesia. Adapun kekurangan Bamboozle dia antaranya fiturnyaÂ sangat terbatas, pembuatan akun pembuat soal dan menjawab soal tidak dibedakan, Tidak ada perizinan akses untuk memulai game, game hanya bisa dimainkan per tim, instrumen pada Bamboozle ini tidak ada, hanya backsound ketika memilih jawabannya saja, Pada saat menggunakan media sangat memungkinkan siswa pasif Sementara kelebihan dari Bamboozle untuk mengakses Bamboozle tanpa harus membuat akun, terdapat soal yang bermacam-macam, dan bisa digunakan untuk tiap jejang pendidikan Bamboozle bisa diakses melalui laptop atau ponsel.Kata Kunci: Baamboozle, bahasa Indonesia; media pembelajaran